Univariate Shepard-Birkhoff Interpolation - Coman, Gheorghe; Trîmbiţaş, Radu T. (Rev. Anal. Numér. Théor. Approx., 2001)
In this paper we study the univariate Shepard-Birkho operators. We give an error estimation for the aproximation with these operators and some examples and graphs.